Pengaruh Ukuran Perusahaan, Umur Perusahaan, dan Investment Account Holder terhadap Pengungkapan Islamic Corporate Social Responsibility (Studi kasus pada Bank Umum Syariah yang terdaftar di Otoritas Jasa Keuangan (OJK) Tahun 2016-2019) - Velly Vionita; Kurnia Kurnia; Febrial Pratama (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2021)
Islamic Corporate Social Responsibility is a reporting of corporate social responsibility using sharia principles. Disclosure of social responsibility must be appropriate based on the values of the concept of Maqashid Shari'ah. For sharia-based companies, use Islamic Social Reporting in reporting corporate social responsibility. The entire implementation of social responsibility that has been carried out by the company will announce it to the public through social disclosure in the annual report issued by the company. This study aimed to determine the effect of company size, company age and Investment Account Holder on Islamic Corporate Social Responsibility disclosure. The population in this study is Sharia Commercial Banks registered with the Otoritas Jasa Keuangan using purposive sampling technique. This analysis techniques in this study is panel data regression. The test result of this study indicated that company size, company age and Investment Account Holder intensity simultaneousy influenced Islamic Corporate Social Responsibility disclosure. Partially, company size intensity positively affected Islamic Corporate Social Responsibility disclosure, while company age and Investment Account Holder did not affect Islamic Corporate Social Responsibility disclosure.